2004
DOI: 10.1149/1.1814011
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of Wet Chemical Treatments on the Surface Roughness of Epoxy Polymer Layers for Buildup Layers

Abstract: The adhesion of plated metal layers to epoxy polymer surfaces is of prime importance for the reliability of interconnections in microelectronics. An increase in the roughness of the polymer surface, caused by chemical treatment, plays an important part in the adhesion strength of plated metal layers by increasing the total area of interaction between both layers. This kinetic study of the influence of chemical treatments on the surface of the polymer consists of two parts. In Part I the kinetics of sweller tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 21 publications
2
37
0
Order By: Relevance
“…This process enables direct electroless copper deposition on a smooth polymer film and could be applicable for manufacturing printed circuits on a flexible film. In common electroless processes, metals are deposited onto a polymer surface that has a micrometer-scale roughness formed by chemical etching [10,11], which can affect the physical properties of the metal film and damage the polymer substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process enables direct electroless copper deposition on a smooth polymer film and could be applicable for manufacturing printed circuits on a flexible film. In common electroless processes, metals are deposited onto a polymer surface that has a micrometer-scale roughness formed by chemical etching [10,11], which can affect the physical properties of the metal film and damage the polymer substrate.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained hybrid films are expected to be metallized by means of electroless plating due to the catalytic activity of the metal nanoparticles. Common electroless processes involve three main steps: i) surface preparation, ii) surface activation or surface seeding with a catalyst, and iii) the electroless plating process itself [10,11]. While surface preparation, such as etching to increase the surface roughness, is necessary to provide good adhesion, it can affect the physical properties of the deposited metal film and damage the polymer substrate.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 The first reaction is the reaction with the trichlorotricyanuryl compound for 24 h; the second treatment is the reaction with the IDA solution. Table III shows that the mass changes are limited to 1.5 wt %.…”
Section: Results Of the Synthesis Reactionsmentioning
confidence: 99%
“…According to Coppens, 16 a fractal surface also influences diffusion of components. In order to maximize adhesion, Wool and Long 15 suggested development of pretreatments that can generate fractal surfaces to which high adhesion by mechanical interlocking could be expected.The kinetics of roughness formation due to wet-chemical treatments was extensively studied in our previous publications, [17][18][19][20] in which the effects of swellers and oxidizers in the bulk of the polymer and on its surface were qualitatively and quantitatively determined. These previous studies revealed a number of synergetic effects between the sweller and oxidizer treatments.…”
mentioning
confidence: 99%
See 1 more Smart Citation